An electrochemical aptasensor based on g-C3N4/Fe3O4/PANI nanocomposite applying cancer antigen_125 biomarkers detection. (April 2023) - Foroozandeh, Amin; Abdouss, Majid; SalarAmoli, Hossein; Pourmadadi, Mehrab; Yazdian, Fatemeh
Abstract: Early detection can help control and treat ovarian cancer, which is one of the most deadly types of cancer among women. Nowadays, nanobiosensors as a time-saving tool with highly selective and sensitive properties applied in different biomarker detection. One of the most sensitive methods for diagnosing ovarian cancer is electrochemistry-based methods. This study was conducted to detect ovarian cancer antigen 125 (CA125) biomarkers using an electrochemical aptasensor based on voltammetric techniques. Graphitic carbon nitrides, magnetic nanoparticles, and polyaniline (g-C3 N4 /Fe3 O4 /PANI) were utilized to stabilize aptamer chains on the surface of a gold electrode (GE). The hexacyanoferrate redox system was used as the electroactive probe, and it was typically operated at around 0.3 V (vs. Ag/AgCl), with a 0.418 U.mL −1 detection limit in the hexacyanoferrate medium. As a redox-active medium, methylene blue was used to lower the electrochemical potential for the detection of CA125. The detection potential was reduced to − 0.2 V, and the electrochemical aptasensor exhibited a broad dynamic linear range (DLR) ranging between 5 and 60 U.mL −1, with an R 2 of 0.993 and a limit of detection (LOD) of 0.298 U.mL −1 . The results revealed that the modified electrode is highly selective for CA125 compared with other biomolecules. Additionally, the synthesized aptasensor exhibited excellent selectivity and stability. This electrochemical aptasensor demonstrated outstanding results for evaluating the serum of patients and healthy people. Graphical Abstract: Scheme 1 The g-C3 N4 /Fe3 O4 /PANI nanocomposite modified with aptamer for CA125 detection. ga1 Highlights: Graphitic carbon nitride (g-C3 N4 )/Magnetic nanoparticles (Fe3 O4 )/Polyaniline (PANI)/gold electrode (GE) was successfully prepared. The nanocomposite can significantly improve electrochemical performance. Electrochemical impedance spectroscopy and Squarewave voltammetry technics are used to detect cancer antigen 125 (CA 125). The sensor has a linear range of 5–60 U.mL −1 with a 0.298 U.mL −1 limit of detection.